Enhanced Performance of Flat Plate Solar Collector with Twisted Tape Double Cutting Rectangle Shape - Basima Salman; Sanaa Hassan Obaid (Journal of Engineering and Sustainable Development)
Solar water heating uses solar collectors to capture sunlight and convert it into heat energy. It has grown remarkably and is now widely used for water heating in homes and manufacturing plants worldwide. Various techniques have been employed to enhance heat transfer in collectors, such as enlarging the collector's surface area or inducing fluid turbulence in the tubes. This article aims to boost the effectiveness of a flat plate solar collector through the use of a twisted strip to generate turbulence in the flow. Three twisted tapes, made of Aluminum and copper, were placed inside the collector's tubes, each with a different shape. All the twisted tape shapes - square, rectangle, and triangle - were identical in size, measuring 1000 mm in length and 1 mm in thickness. Both experimental tests and a numerical study were conducted on these three shapes of twisted tape. For each shape, three pitches were used: 2,3 and 4 cm. The results indicated that the efficiency of the collector using the double-cutting rectangular twisted tape with a 2 cm pitch was superior to other collector shapes. Moreover, the copper tapes exhibited greater efficiency than the aluminum tapes.